On the Development of Vehicle Dynamics Active Systems: The Handling Stability Ratio as a Strategic Indicator for Integrating Multiple Actuators - Roberto Aratri; Stefano de Pinto; Giuseppe Guastadisegni; Antonio Gonzalez; Aldo Sorniotti; Francesco Bottiglione; Giacomo Mantriota (IEEE Access)
Mechatronic systems for enhancing vehicle dynamics are a widely studied topic, especially in relation to high-performance vehicles, which must be characterized by high levels of handling capability and stability, as well as “natural” driving behavior. Despite the broad availability of research on the integration and control of multiple active systems, there is a lack of discussion on how they can effectively extend the range of achievable vehicle performance. To address the gap, this paper introduces and analyzes a novel performance indicator, the Handling Stability Ratio (HSR). HSR is the ratio of the maximum lateral grip level of the rear axle to that of the front one, and can be computed along the ISO open-loop steady-state circular tests. By means of HSR, it is possible to quantify the relative axle force reserve that is available for exploitation by an active system. The study considers how different chassis control actuations, namely Front Active Camber (FAC), Rear Active Camber (RAC), Rear Wheel Steering (RWS), and Rear Torque Vectoring (RTV), can virtually vary HSR, thereby increasing the cornering or stability performance in limit handling conditions, compared to the corresponding passive vehicle. In the initial vehicle setup phase, HSR can be adopted for obtaining the vehicle-level performance limit, and, when coupled to the actuator limits, provides the feasibility range of the considered chassis actuation suite.